MEMAHAMI ANTROPOLOGI STRUKTURAL CLAUDE LEVI-STRAUSS - Gusti A. B Menoh (Cakrawala Jurnal Penelitian Sosial, 2013)
French structuralism pioneered by Saussure. The term structure is always pointing to the understanding of language as a system. By the school of Prague (Jacobson and Trubetzkoy) term structure refers to the understanding of the structure of a system Saussurean structural linguistic methods would also schools of Prague is then influenced Levi-Strauss. Levi-Strauss develop the linguistic methods and apply them in social anthropology, so the approach is called structuralism ethnological or anthropological structural. In this approach, (1) Relation decisive difference. Culture is seen as grammar, and task analysis of the cultural phenomenon is no longer understand the symptoms of the particular separate / distinct, but found "hidden code grammatical" that makes every symptom particular it has a meaning in relationship-difference with symptoms particular as the whole system marker. (2) The emphasis on synchronous approach. Following the view Saussure that the meaning of a term defined by his relations at a given point in time, which is synchronous with other terms, Levi-Strauss argued relations a cultural phenomenon with phenomena other at certain point of time is what determine the meaning of the phenomenon. So relations sinkronislah decisive, not the diachronic. The identity of a person / group of people seemed to only be identified through distinction from the other. Always understood identity is relational. Humans know himself in meetings and interactions with the world and other people. I'm me, precisely because there is the other, who is different from me.Keywords: French structuralism, Structural Anthropology, Levi-Strauss, Identity